How informed are german patients with pulmonary sarcoidosis about their disease? - Buschulte, Katharina; Höger, Philipp; Ganter, Claudia; Wijsenbeek-Lourens, Marlies; Kahn, Nicolas; Kriegsmann, Katharina; Wilkens, Finn M.; Polke, Markus; El-Hadi, Sarah; Lederer, Christoph; Herth, Felix; Kreuter, Michael (Respiration, 2023)
Background: Sarcoidosis is a multisystemic disease with a heterogenous course of disease. Comprehensive information about the complexity and treatment indications is essential for improving patient knowledge and adhering to therapy. Objectives: The aim of our study was to investigate the level and resources of information in patients with sarcoidosis and to analyze differences in patient subgroups including age and gender. Methods: We conducted a questionnaire-based online survey in Germany and three semi-structured focus group interviews. The interviews were evaluated independently by two investigators using a structured qualitative content analysis. Results: A total of 402 completed questionnaires were analyzed, 65.8% of participants were women, and the mean age was 53 years. The majority of patients felt well informed about their disease in general (59.4%), but 40.6% were inadequately informed. The most relevant information gaps related to the future perspective (70.6%) as well as fatigue and diffuse pain (63.9%). Most patients received information from their treating pulmonologist (72.1%). 94% used the internet, especially homepages of patient support groups (75.2%). Male participants more often reported being well informed about their disease and were more satisfied with the information (p = 0.001). During the interviews, patients expressed their wish for more comprehensive information and highlighted the importance of psychological co-care as well as the future perspective. Conclusions: A relevant proportion of patients with sarcoidosis are inadequately informed about their own disease, particularly with regard to factors impeding quality of life such as fatigue. Efforts are needed to improve the level and quality of information.